Hubungan Keterlibatan Ayah dengan Stres Akademik pada Siswa Laki-Laki Sekolah Menegah Kejuruan - Putri Ratna Sari; Rahmi Lubis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
Academic stress is one of the challenges that adolescents may experience when facing various demands in the educational process. One factor associated with students’ ability to cope with such pressures is father involvement in their lives. This study aimed to examine the relationship between father involvement and academic stress among male students. The study employed a quantitative approach with a correlational design. The participants consisted of 94 male students who met the research criteria. Data were collected using a father involvement scale and an academic stress scale. Data were analyzed using Spearman’s Rank correlation because the research data were not normally distributed. The results showed that the mean score for father involvement was 42.00 with a standard deviation of 8.839, while the mean score for academic stress was 40.01 with a standard deviation of 6.716. The majority of respondents were in the moderate category for both father involvement and academic stress. The correlation analysis revealed a significant negative relationship between father involvement and academic stress (? = -0.202; p = 0.025). This finding indicates that higher levels of father involvement are associated with lower levels of academic stress among male students. Although the strength of the relationship was low, the findings indicate that father involvement is associated with students’ psychological conditions in dealing with academic demands.